THE POSTPONED TREATMENT OUTCOMES IN PULMONARY TUBERCULOSIS PATIENTS AFTER RADICAL PULMONARY RESECTION - P. V. Rogozhkin; E. A. Borodulina (Туберкулез и болезни лёгких)
The objective of the study: to investigate the efficiency of surgical treatment in pulmonary tuberculosis patients and to define main risk factors of tuberculosis re-activation in those who had surgeryMethods The postponed surgery results (in 6-7 years) were investigated in 273 patients, who were operated in 2010-2011 Two groups were formed: Group 1 included patients taken off the register due to recovery, Group 2 included patients who had relapse or exacerbation of the disease after the surgery Those taken off the register due to some other reasons were not included in the comparative analysisResults. It was proved that postponed treatment efficiency exceeded 90% Tuberculosis re-activated in 77% of cases, in those with multiple and extensive drug resistance (533%), lung tissue destruction (62%), fibrous-cavernous tuberculosis (333%), concurrent conditions (524%) and complications in the early post-operative period (95%)  The re-activation occurred more often after large surgeries including consecutive corrective thoracoplasty Should there be indications for surgery, it is sensible to decide about the surgery within the 1st year of follow-up.